(untitled) (ex æquo, 2023)
The Absence of Legal Recognition of Trans-Parenting in Portugal With the approval of Law no. 38/2018, of 7 August, which established the right to self-determination of gender identity and expression, it became materially possible that the genital sex no longer corresponds to the legal sex. Since the parenting regime is closely related to the sex registered in the civil registry, this article intends to explore the legal gap that resulted from the lack of harmonization and articulation between these two legal regimes. To this end, the author seeks to characterize the parenting regime in the Portuguese legal system, to understand the effects of Law no. 38/2018 on the parenting regime and to identify the international precepts and constitutional principles that are involved in this matter.